Wayne E. Oates Papers - Z. Smith Reynolds Library Special Collections and Archives (My University, 2012)
Inventory of the Wayne E. Oates Papers.
Keywords: Oates, Wayne E. (Wayne Edward); Oates, Wayne E. (Wayne Edward), 1917-1999, 1917-1999